ChemInform Abstract: Kinetics vs. Thermodynamics: A Unique Crystal Transformation from a Uranyl Peroxo‐Nanocluster to a Nanoclustered Uranyl Polyborate. Issue 49 (9th December 2014) - Zhang, Yingjie; Bhadbhade, Mohan; Price, Jason R.; Karatchevtseva, Inna; Collison, David; Lumpkin, Gregory R.
Abstract Reaction of UO2(NO3)2, NaOH, H2O2, and H3BO3 in aqueous solution leads to the formation of yellow crystals of Na14 [(UO2)(O2)1.5] 28·nH2O (I) at pH 8.5 within a few days, followed by transformation of (I) at room temperature to light yellow‐green crystals of Na6 [UO2B16O24(OH)8] ·14H2O (II) (<80% yield).